The Legal Risks for Investors Due to Market Manipulation in the Cryptocurrency Market - Fajar, Rahula; Sugiyono, Heru (Law Development Journal, 2023)
This study aims to explore the intricate legal landscape surrounding the cryptocurrency market in Indonesia, specifically addressing the prevalent challenges and risks of market manipulation. The writing method is anchored on a comprehensive examination of primary, secondary, and tertiary legal resources, including pivotal legislations such as the Capital Market Regulation (UUPM) and various other Indonesian laws. Furthermore, a library research technique has been employed, drawing from a broad spectrum of theoretical studies, past literature, and expert opinions to provide a holistic understanding of the subject. The novelty of this study emerges from its specialized focus on market manipulation within the rapidly evolving context of the Indonesian cryptocurrency realm. This focus differentiates it from more generic studies on cryptocurrency, offering tailored insights and recommendations for the Indonesian scenario. Based on the research undertaken, we conclude that Indonesia's strategic and proactive legal measures, coupled with the inherent advantages of regulated cryptocurrency platforms, play a pivotal role in countering market manipulation risks. For the practical application of these findings, it is imperative for Indonesian policymakers and regulatory entities to sustain an adaptive approach, ensuring continuous monitoring and timely updates to the legal frameworks. This adaptability guarantees their resonance with the ever-shifting paradigms of the cryptocurrency domain. Additionally, the research underscores the significance of robust investor education initiatives and advocates for a synergistic collaboration between regulatory bodies, cryptocurrency platforms, and the broader investor community. Such collaborative efforts are instrumental in nurturing a transparent, secure, and resilient cryptocurrency environment in Indonesia, setting a benchmark for similar emerging markets globally.